Pengembangan Media Pembelajaran Interaktif Berbasis Video Tutorial Di Sekolah Menengah Kejuruan - Maenuddin Bustanil S; Asrowi; Deny Tri Adianto (Jurnal Teknologi Pendidikan)
Abstract: The rapid exchange of information through multimedia throughout the world helps the growth of humans’ knowledge and, at the same time, requires redefinition of learning methods and media, especially in the field of vocational education. The purpose of this research was to develop an interactive learning media in the form of video tutorial in increasing the learning effectiveness in the subject of audio processing techniques at class XII in multimedia competence in one of the State Vocational Schools in Parepare. Research and Development method was used in this study. The stages of research included the planning, design and development stages. The subjects engaged in this research were two validators namely the experts of learning media and learning material, the students of class XII multimedia with the total of 18 persons, and one teacher who taught audio processing techniques. The results achieved in the development of interactive media showed that the developed video tutorial media had been valid based on the assessment of both learning media and learning material experts. The tests conducted on individuals, small group trials, and the subject teacher’s responses indicated that an interactive media in the form of video tutorial was effective and appropriate to the users’ needs.